Mindfulness-Based Cognitive Therapy (MBCT) Enhancing Emotion Regulation In Adults: A Scoping Review - Septiani, Haryati; Ainun Najib Febrya Rahman; Hanafi; Devi Harmita; Muhammad Luthfi; Dwin Seprian (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Mental disorders are a growing public health concern, with emotional regulation playing a crucial role in maintaining psychological well-being. Mindfulness Based Cognitive Therapy (MBCT) is a structured intervention that combines mindfulness practices with cognitive therapy to enhance emotional regulation. This scoping review aims to analyze the effectiveness of MBCT in improving emotional regulation in adults and to identify the specific aspects most influenced by the intervention. Using the Arksey and O’Malley framework, a systematic search was conducted in the Scopus and Web of Science databases for studies published between 2015 and 2025. Four quantitative studies met the inclusion criteria. The findings show that MBCT improves several emotional regulation components, including impulse control, emotional awareness and clarity, acceptance of emotional responses, and reduction in rumination. These improvements contribute to better emotional stability and resilience among adults facing psychological distress. The review supports the use of MBCT as a comprehensive therapeutic approach that promotes adaptive emotional responses and long term mental health. MBCT has the potential to be implemented in both clinical and community mental health settings as a preventive and promotive strategy.